An experimental and numerical analysis for stiffened composite panel subjected to shear loading in hygrothermal environment. (15th March 2016) - Zhang, Tiejun; Li, Shulin; Chang, Fei; Shi, Xiaopeng; Li, Lekun
Abstract: This paper presents a detailed experimental and numerical investigation on absorption and shear behaviors of stiffened composite panel subjected to hygrothermal environment. Due to the special and complex configurations of stiffened composite panel, water diffusion process should be divided to two absorption phases. Compared to conventional single equation by Fick's law, two absorption equations in this model could describe the absorption curve of experimental result perfectly. The combination of empirical formulae and finite element model is used to study buckling and postbuckling behavior for stiffened composite panel subjected to shear loading in hygrothermal environment. The buckling loads and failure loads of unaged specimens decreased approximately 10% and 25%. Good agreement between experimental data and numerical results is observed. According to experimental and numerical results, failure modes of the hygrothermal specimens include panel cracks and debonding of stiffeners.